Hydroelectric Power Plants ’ Re Servoirs And Their Impact On The Environment (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper presents the analysis of different types of impact the hydroelectric power plants’ reservoirs could make on the environment. Hydroelectric power plants (HPP) produce ecologically safe energy and correspond to the modern striving for sustainability because they are operated on renewable energy sources. At the same time they can provoke various potential dangers for the environment. The objective of the investigation is to demonstrate the interrelation between the type and structure of a hydroelectric power plant and the way its reservoir may impact on the nature surrounding the plant. These effects may be direct and indirect, positive and negative and vary from insignificant that can be easily fixed to those that are irreversible and catastrophic. The latter should be taken into account during the design of HPP.